Strategi Adaptif NGO saat Pandemi COVID 19 (Studi Kasus Pelayanan Sosial Mitra Wacana Women Resource Centre) - Hidayah, Nahdiyana Fitri (Jurnal Publisitas, 2021)
Mitra Wacana WRC is an organization engaged in the issue of women and children to fight for gender justice, and an institution that works more at the mezzo and macro levels. Mitra Wacana means an organization that can be critical thinking partners of women and children. In this pandemic condition, Mitra Wacana WRC is trying to adapt by minimizing physical contact. Managers and institutional members have agreed to carry out online-based activities and coordination, such as routine meetings that are usually carried out in physical meetings, which are now carried out by utilizing online media such as WhatsApp groups. The research method used is qualitative descriptive. Praktikan conduct the interview process in order to gain understanding and disclosure that is being faced by the institution. This study examines the adaptive strategies of NGOs in the event of the COVID 19 pandemic, a case study in the social services of Mitra Wacana WRC. The impact felt due to this pandemic every member of the community and beneficiaries (clients) began to get used to utilizing existing technology in obtaining information and coordinating. Because basically Mitra Wacana continues to carry out its usual activities in the midst of the coronavirus situation.